Resource Availability as Driving Factor of the Reproductive Mode in Soil Microarthropods (Acari, Oribatida) - Wehner, Katja (Public Library of Science, 2014)
The availability of high quality resources is an important factor driving community structure and reproductive mode of animals. Parthenogenetic reproduction prevails when resources are available in excess, whereas sexuality correlates with resource shortage. We investigated the effect of resource availability on the community structure of oribatid mites in a laboratory experiment. Availability of food resources was increased by addition of glucose to leaf litter and reduced by leaching of nutrients from leaf litter. Experimental systems were incubated at three different temperatures to establish different regimes of resource exploitation. Community structure of oribatids and numbers of eggs per female were measured over a period of ten months. We expected the density of oribatid mites to decline in the reduced litter quality treatment but to increase in the glucose treatment. Both effects were assumed to be more pronounced at higher temperatures. We hypothesized sexual species to be less affected than parthenogenetic species by reduced resource quality due to higher genetic diversity allowing more efficient exploitation of limited resources, but to be outnumbered by parthenogenetic species in case of resource addition due to faster reproduction. In contrast to our hypotheses, both sexual and parthenogenetic oribatid mite species responded similarly with their densities declining uniformly during incubation. The parthenogenetic Brachychthoniidae and Tectocepheus dominated early in the experiment but were replaced later by parthenogenetic Desmonomata and Rhysotritia. In parthenogenetic species the number of eggs per female increased during the experiment while the number of eggs in sexual females remained constant or decreased slightly; in general, egg numbers were higher in sexual than in parthenogenetic species. The results indicate that for sustaining oribatid mite populations other resources than litter and associated saprotrophic microorganisms are needed. They also indicate that there are two groups of parthenogenetically reproducing species: exploiters of easily available resources and consumers of leaf litter associated resources.